Concept of Takaful and its application in HSBC Amanah Takaful (Malaysia) / Nur Musfirah Ismail - Ismail, Nur Musfirah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Takaful is an Islamic insurance with Islamic rulings or Shariah compliance based on AlQuran and As-Sunnah as the main sources. The aim of this paper is to explore about the idea of the concept and applications of takaful in HSBC Amanah Takaful which is located at Lebuh Ampang, Kuala Lumpur. This research will increase the understanding of the society to acknowledge about takaful which is a part in Islamic finance. Even though takaful is not a new thing that had been introduced in the finance, but still there are some groups of people who does not clearly understand about the concept of takaful and the way to apply and relate it in their life as they are not fully aware with the benefits that come up with the takaful itself. This paper will also discussing about the related issues and challenges occurred in the application of takaful among the society.